Evaluating hydrogen bonding control in the diastereoselective Diels–Alder reactions of 9-(2-aminoethyl)-anthracene derivatives. Issue 42 (4th September 2015) - Bawa, R. A.; Gautier, F.-M.; Adams, H.; Meijer, A. J. H. M.; Jones, S.
Abstract : Hydrogen bonding can be used to control the stereoselectivity of the cycloaddition of some anthracene derivatives. DFT calculations provide support for the origins of the selectivity in these reactions. Abstract : Several 9-(2-aminoethyl)anthracene derivatives were prepared with different nitrogen substitutents including alkyl, acetamide, trifluoroacaeamide and t -butyl carbamate. The selectivity in Diels–Alder cyclodaddition reaction with N -methyl maleimide was evaluated through single crystal X-ray analysis of the products. Models for the change in selectivity with hydrogen bond acceptor are proposed, supported by DFT level calculations.